Influence of Social Media on Employee Engagement and Organizational Culture in the Field of Human Resources Management - Norliani; Iswahyu Pranawukir; Suci Rahmadani; Siti Hasanah; Siti Aniqoh Shofwani (Politeknik Ganesha Medan, 2024)
The development of information technology, particularly social media, has transformed communication in the workplace. Employees increasingly utilize social media platforms to interact and share information, both internally and externally within the company. This research aims to analyze the influence of social media on employee engagement and organizational culture in the field of Human Resources Management (HRM). The research method employed is a qualitative literature review utilizing Google Scholar to gather data from articles, papers, and journals published between 2000 and 2024. The study findings indicate that social media has a significant impact on employee engagement and organizational culture in the field of HRM. By facilitating communication among employees and strengthening the relationship between management and employees, social media can enhance employee engagement and shape an inclusive and collaborative organizational culture.